Serratia Secondary Metabolite Prodigiosin Inhibits Pseudomonas aeruginosa Biofilm Development by Producing Reactive Oxygen Species that Damage Biological Molecules - Kimyon, Önder; Das, Theerthankar; Ibugo, Amaye I.; Kutty, Samuel K.; Ho, Kitty K.; Tebben, Jan; Kumar, Naresh; Manefield, Mike (Frontiers in Microbiology, 2016)
Prodigiosin is a heterocyclic bacterial secondary metabolite belonging to the class of tripyrrole compounds, synthesized by various types of bacteria including Serratia species. Prodigiosin has been the subject of intense research over the last decade for its ability to induce apoptosis in several cancer cell lines. Reports suggest that prodigiosin promotes oxidative damage to double-stranded DNA (dsDNA) in the presence of copper ions and consequently leads to inhibition of cell-cycle progression and cell death. However, prodigiosin has not been previously implicated in biofilm inhibition. In this study, the link between prodigiosin and biofilm inhibition through the production of redox active metabolites is presented. Our study showed that prodigiosin (500 µM) (extracted from Serratia marcescens culture) and a prodigiosin/copper(II) (100 µM each) complex have strong RNA and dsDNA cleaving properties while they have no pronounced effect on protein. Results support a role for oxidative damage to biomolecules by H2O2 and hydroxyl radical generation. Further, it was demonstrated that reactive oxygen species scavengers significantly reduced the DNA and RNA cleaving property of prodigiosin. P. aeruginosa cell surface hydrophobicity and biofilm integrity were significantly altered due to the cleavage of nucleic acids by prodigiosin or the prodigiosin/copper(II) complex. In addition, prodigiosin also facilitated the bactericidal activity. The ability of prodigiosin to cause nucleic acid degradation offers novel opportunities to interfere with extracellular DNA dependent bacterial biofilms.